COMMUNITY DEVELOPMENT MODEL IN PREVENTING RADICALISM TO IMPROVE SECURITY IN BANDAR LAMPUNG CITY - Sonep, Moch; Romli, Khomsahrial; Syukur, Abdul; Budimansyah, Budimansyah; Setiawati, Rini (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This research focuses on efforts to explore community development models as a strategy to prevent radicalism in the city of Bandar Lampung. By detailing the local social context, the research aims to provide concrete insight into the role of society in reducing the potential for radicalism. Through a comprehensive approach, this research is expected to provide a valuable contribution to designing prevention strategies that can be adopted on a sustainable basis. This research uses a qualitative case study method. Data was obtained from in-depth interviews and observations of community development activities, with the primary respondents directly involved. Secondary data sources involve documents related to development programs and radicalism prevention policies. Data collection tools include interview guides, field notes, and data analysis using coding and categorization. Data validity is enforced through triangulation, ensuring the accuracy of findings through comparison of interviews, observations and documents. The research results confirm that three models involving the Brimob Unit in Bandar Lampung City—prevention of radicalism, guidance, and cooperation—have proven their effectiveness in improving community security. The radicalism prevention model has succeeded in increasing public awareness and strengthening awareness of the potential threat of radicalism. The development of Brimob Units provides positive results by improving members' skills and strengthening relationships with local communities. The collaborative model in community development has proven effective through an inclusive approach that increases community awareness and skills in preventing radicalism.